Objective vs. subjective evaluation of cognitive performance during 0.4-MPa dives breathing air or nitrox - Germonpré, P.; Balestra, C.; Hemelryck, W.; Buzzacott, Peter; Lafère, P. (2017)
© by the Aerospace Medical Association, Alexandria, VA. BACKGROUND: Divers try to limit risks associated with their sport, for instance by breathing enriched air nitrox (EANx) instead of air. This double blinded, randomized trial was designed to see if the use of EANx could effectively improve cognitive performance while diving. METHODS: Eight volunteers performed two no-decompression dry dives breathing air or EANx for 20 min at 0.4 MPa. Cognitive functions were assessed with a computerized test battery, including MathProc and Ptrail. Measurements were taken before the dive, upon arrival and after 15 min at depth, upon surfacing, and at 30 min postdive. After each dive subjects were asked to identify the gas they had just breathed. RESULTS: Identification of the breathing gas was not possible on subjective assessment alone, while cognitive assessments showed significantly better performance while breathing EANx. Before the dives, breathing air, mean time to complete the task was 1795 ms for MathProc and 1905 ms for Ptrail. When arriving at depth MathProc took 1616 ms on air and 1523 ms on EANx, and Ptrail took 1318 ms on air and and 1356 ms on EANx, followed 15 min later by significant performance inhibition while breathing air during the ascent and the postdive phase, supporting the concept of late dive/postdive impairment. DISCUSSION: The results suggest that EANx could protect against decreased neuro-cognitive performance induced by inert gas narcosis. It was not possible for blinded divers to identify which gas they were breathing and differences in postdive fatigue between air and EANx diving deserve further investigation.